Faktor-faktor yang Berhubungan dengan Kecelakaan Kerja pada Operator Dump Truck di PT. X Kabupaten Kutai Timur - Kirana, Anindya Sashi; Sultan, Muhammad; Lestari, Ida; Ramdan, Iwan Muhamad; Hardianti, Dewi Novita (UI Scholars Hub, 2025)
Coal mining is one of the industries that has a high level of danger and risk of work accidents. In 2023, in PT X department Z there were 36 work accidents with the most units occurring in the dump truck unit. The purpose of this study was to determine the factors associated with work accidents in dump truck operators at PT X East Kutai Regency in 2025. This study used a cross sectional study design with 78 respondents who were dump truck operators taken by stratified random sampling. Data collection using questionnaires and CMR (Compliance Monitoring Report) observation sheets that apply at PT.X. Measurement of variables using the Guttman scale based on K3 theory and adaptation of previous research. Data analysis using Spearman rank correlation analysis, the dependent variable is work accidents, and the independent variables include OHS knowledge, OHS training, compliance with SOPs, length of service, work shifts. In this study, 30.8% of workers had experienced work accidents. The results of the bivariate test showed that there was a significant relationship between OHS knowledge (pvalue=0.000), OHS training (p value=0.015), compliance with SOP (p value=0.003) with the incidence of work accidents in dump truck operators. Meanwhile, there was no relationship between the variables of length of service (p value=0.619) and work shift (p value=0.213) with the incidence of work accidents among dump truck operators.